PATIENTS PROFILE AT THE SLEEP APNEA OUTPATIENT CLINIC AT A UNIVERSITY HOSPITAL - Damasceno Inácio, Natania Tuanny; Silva, Juliane Patrícia Grigório da; Ferreira, Lidiane Maria de Brito Macedo; Fernandes, Alexandre Augusto (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Introduction: Obstructive sleep apnea syndrome (OSAS) is characterized by recurrent collapses of the pharyngeal region during sleep, resulting in a substantial reduction in airflow (apnea and hypopnea), despite respiratory efforts. Objective: To report the profile of patients referred to the Sleep Apnea Outpatient Clinic of Hospital Universitário Onofre Lopes (HUOL), emphasizing on the main risk factors associated with OSAS. Methodology: It is retrospective study, cross-sectional, in which data obtained by reviewing medical records of patients seen at the sleep apnea outpatient clinic between 2017 and 2019 were used. Results: Medical records of 43 patients were evaluated, being (62, 8%) male and (37.2%) female. All patients underwent previous screening before polysomnography, being divided into three groups: Group I - with mild OSAS: 8 patients (18.6%); Group II - with moderate OSAS: 18 patients (41.8%); Group III - with severe OSAS: 17 patients (39.5%). Conclusion: Sleep apnea syndrome is commonly correlated with metabolic syndrome.